PRIVATE PROPERTY AND GOVERNMENTALITY IN CHINA, AN APPROACH. (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
This paper offers an approach to the study of private property in contemporary China from the point of view of governmentality (Foucault). Based on a brief reconstruction of the main legal and political events that gave greater prominence to private property, the paper analyses some characteristics of this right within the framework of the Chinese Communist Party's (CCP) art of government. The analysis shows, taking up the contributions of governmentality, that the recognition of private property not only responds to measures of economic liberalisation, but also to a government practice that seeks, by indirect means, to strengthen the State and the Party. The paper is organised in three parts. The first part reconstructs the main legal and political measures that led the CCP to legally recognise private property in 2007. The second part provides a brief analysis of private property and Chinese socialism, introducing Michel Foucault's genealogy of neoliberalism. The last part highlights the contributions of the notion of governmentality to the analysis of private property in contemporary China.
Keywords: private property; China; governmentality; CCP.